2020
DOI: 10.2196/preprints.20417
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing Web-Based Platforms for Promoting HIV Self-Testing and Pre-Exposure Prophylaxis Uptake in High-Risk Men Who Have Sex With Men: Protocol for a Longitudinal Cohort Study (Preprint)

Abstract: BACKGROUND The majority of those living with human immunodeficiency virus (HIV) are men who have sex with men (MSM), and young, minority MSM account for more new HIV infections than any other group. HIV transmission can be reduced through detection and early treatment initiation or starting pre-exposure prophylaxis (PrEP), but rates of testing are lower than recommended among MSM and PrEP uptake has been slow. Although promoting HIV testing and PrEP uptake by placing advertisements on w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…A review of HIV-focused social media interventions revealed increased access to information and enhanced ability to communicate (Cao et al, 2017). These interventions also provided anonymity, fostered virtual community, and expanded geographical reach (Lemley et al, 2020).…”
mentioning
confidence: 99%
“…A review of HIV-focused social media interventions revealed increased access to information and enhanced ability to communicate (Cao et al, 2017). These interventions also provided anonymity, fostered virtual community, and expanded geographical reach (Lemley et al, 2020).…”
mentioning
confidence: 99%